2021
DOI: 10.31557/apjcp.2021.22.2.633
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Immunoexpression of Opioid Receptors and their Correlation with Markers of Angiogenesis, Cell Proliferation and Apoptosis in Breast Cancer

Abstract: Objective: Breast cancer is a disease of great concern. The prognosis of this tumor is related to its staging. Opioids are widely used to minimize pain in oncology clinics; however, the relationship between the administration of opioids and their effects on tumor cells has yet to be elucidated. Therefore, this study aimed to evaluate the immunoexpression of mu-(μ) and kappa-(κ) opioid receptors and their correlation with markers of angiogenesis, cell proliferation, and apoptosis in biopsies of breast tumors. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Also, B2AR antagonist PRO decreased proliferation, migration and invasion of TNBC and non-TNBC cells both in vitro and in vivo systems [ 11 , 29 , 57 , 58 ]. In the case of MOR signaling, significant predominance of Ki-67 and μ-opioid receptor immuno-expression in the lymph nodes was observed in breast cancer patients with opioid medications [ 59 ]. Also, MOR antagonist naloxone or naltrexone increased the cell death while decreased the cell metastasis in an animal model of TNBC [ 29 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, B2AR antagonist PRO decreased proliferation, migration and invasion of TNBC and non-TNBC cells both in vitro and in vivo systems [ 11 , 29 , 57 , 58 ]. In the case of MOR signaling, significant predominance of Ki-67 and μ-opioid receptor immuno-expression in the lymph nodes was observed in breast cancer patients with opioid medications [ 59 ]. Also, MOR antagonist naloxone or naltrexone increased the cell death while decreased the cell metastasis in an animal model of TNBC [ 29 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in expression of μ, δ, or κ-opioid receptors in cancer cells or tissues are reported in various cancer types and overall, point to an increased expression in cancer. The majority of studies described an increase in μOR ( 18 22 ), while some reports showed no significant differences in μOR expression levels between the tumour and adjacent non-tumour tissues ( 23 , 24 ). No studies reported a decreased expression of OR in cancer.…”
Section: Opioid Receptor Expression In Various Cancer Typesmentioning
confidence: 99%